From Likes to Buys: Unveiling the Impact of Social Media Influencers on Consumer Behavior and Market Dynamics - Samala, Agariadne Dwinggo; Rawas, Soha (TEM Journal, 2024)
This study investigates the significant impact of social media influencers on consumer purchasing behavior, focusing on the role of credibility and trustworthiness. A robust quantitative research approach was used to collect data from an online survey of 500 consumers who actively follow social media influencers. The results show a significant and positive relationship between social media influencers and consumer purchasing behavior. Notably, the credibility of these influencers and the nature of the products or services they promote emerge as important factors influencing consumer decisions. This study offers useful insights for marketers, emphasizing the importance of strategically selecting influencers and cultivating long-term relationships to increase credibility and trustworthiness. These findings provide practical advice for improving influencer marketing strategies and engaging with target audiences.